Pharmacological blockade of the CD39/CD73 pathway but not adenosine receptors augments disease in a humanized mouse model of graft‐versus‐host disease. Issue 6 (29th April 2019) - Geraghty, Nicholas J; Watson, Debbie; Sluyter, Ronald
Abstract: Allogeneic hematopoietic stem cell transplantation is a curative therapy for a number of hematological malignancies, but is limited by the development of graft‐ versus ‐host disease (GVHD). CD39 and CD73 form an ectoenzymatic pathway that hydrolyzes extracellular adenosine 5′‐triphosphate (ATP) to adenosine, which respectively exacerbate or alleviate disease in allogeneic mouse models of GVHD. The current study aimed to explore the role of the CD39/CD73 pathway and adenosine receptor (AR) blockade in a humanized mouse model of GVHD. Immunodeficient nonobese diabetic‐severe combined immunodeficiency‐IL‐2 receptor γ null mice were injected with human peripheral blood mononuclear cells, and subsequently injected with the CD39/CD73 antagonist αβ‐methylene‐ADP (APCP) (50 mg kg −1 ) or saline for 7 days, or the AR antagonist caffeine (10 mg kg −1 ) or saline for 14 days. Mice predominantly engrafted human CD4 + and CD8 + T cells, with smaller proportions of human regulatory T cells, invariant natural killer T cells, monocytes and dendritic cells. Neither APCP nor caffeine altered engraftment of these human leukocyte subsets. APCP (CD39/CD73 blockade) augmented GVHD as shown through increased weight loss and worsened liver histology, including increased leukocyte and human T‐cell infiltration, and increased apoptosis. This treatment also increased serum human IL‐2 concentrations and decreased the frequency of human CD39 −  CD73 −  CD4 + T cells. In contrast, caffeine (AR blockade) did not alter GVHD severity or human serum cytokine concentrations (IL‐2, IL‐6, IL‐10 or tumor necrosis factor‐α). In conclusion, blockade of CD39/CD73 but not ARs augments disease in a humanized mouse model of GVHD. These results indicate that CD39/CD73 blockade maintains sufficient extracellular ATP concentrations to promote GVHD in this model. Abstract : Humanized NSG mice injected with the CD39/CD73 inhibitor APCP (50 mg kg −1 ) exhibited greater weight loss than saline‐injected mice over 10 weeks. APCP‐injected mice demonstrate greater leukocyte infiltration and histological damage in livers compared with saline‐injected mice. APCP‐injected mice demonstrate greater serum human IL‐2 concentrations compared with saline‐injected mice.